ANALYSIS OF WORKS DEVOTED TO THE STUDY OF THE SHAPE OF THE TRANSVERSE PROFILE OF THE WORKING BODIES OF THE MOLDBOARD TYPE - Khankelov T. K.; Mukhitdinov A. S.; Alimov T.Y. (Galaxy International Interdisciplinary Research Journal, 2022)
The article is devoted to the analysis of works devoted to the study of the shape of the transverse profile of earth-moving machines, in particular, bulldozers. On the basis of the in-depth analysis of studies devoted to the substantiation of the basic parameters concerning the shape of the cross profile the conclusion is made that, despite the numerous works on the substantiation of the basic parameters of the blade, the issues of influence of the shape of the cross profile of the blade on the energy intensity of digging the ground are insufficiently considered.